Про узагальнену гіпергеометричну функцію Гаусса та її застосування - Вірченко, Н.О.; Рум’янцева, О.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The-generalized Gauss hypergeometric function is considered, and the basic properties of this function are investigated. Some applications of this function, in particular, to the solution of a Fredholm integral equation of the first kind are given.